An analysis of land use options and strategies for food availability and land conservation in Yogyakarta, Indonesia - Partoyo; Shrestha, Rajendra Prasad; Shivakoti, Ganesh P.; Tripathi, Nitin Kumar; Sartohadi, Junun; Directorate General of Higher Education (DIKTI); The Ministry of Education and Culture of Republic of Indonesia (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
Population growth and economic development are critical factors of land use change. As the human population increased, demand not only for food but also for residential and other built environments has increased, which possess as a threat to the sustained food availability and environment. In Indonesia, agricultural land conversion to non-agricultural use has been alarming during the last three decades. Recognizing this problem, the Indonesian Government has set regulation for limiting and/or preventing the anticipated conversion of fertile agricultural land to non-agricultural use in three Indonesian provinces, including Yogyakarta. Yet, the conversion of land use is ever continuing uncontrollably. This research was conducted in Yogyakarta, which is experiencing rapid land use change and the policy measures have been implemented in the area to address the problem related land use change. The study objectives were to understand the land use change in the study area during 1992-2004 and 2004-2009 and to project future land use based on empirical trends. Remote sensing and GIS techniques were used to identify and quantify land use change. Combined with household survey data, the driving factors of land use change, especially the conversion of paddy fields to built-up land, were analyzed. Scenarios were created based on identified drivers, trends of land demand and related land use policies, and were used to project land uses by 2029 using the Dyna-CLUE to eventually study the impact of prescribed land use options and strategies on future land use in relation to food availability and land conservation. The observed land use change in the study area was mainly the decrease of wet agricultural land and mixed gardens and increase of built-up areas and dry agricultural lands. Wet agricultural land decreased by about 88 km2 from 527 km2 in 1992 to 439 km2 in 2009, although a slight increase occurred during the brief period from 2004-2009 due to the slight expansion of irrigated paddy fields. The high-density built-up areas were converted mainly from low-density built-up areas. Meanwhile, the increased low-density built-up area was converted from mixed gardens, dry agricultural land or wet agricultural land. The probability of wet agricultural land conversion to built-up area was higher mainly at locations which are distant to city center, close to asphalt road, has low population density, lower elevation, is suitable for rice cultivation, has irrigation support, or does not belong to SG/PAG (Yogyakarta Sultanate land). Meanwhile, the possibility of household decision on wet agricultural land conversion will be higher for households with higher revenue from farming activity, i.e. farm households with large land holdings, higher socioeconomic status, less informed about land related regulations, low viability of farming activity, negative perception of farmland protection, and secure land tenure. Considering potential of land for rice production, 22% of the study area was found to be high potential land, however less than 39% of the existing paddy field in 2009 was located on high potential land. The rest was located on land with lower class potential. Meanwhile, 20% of land among the total high potential land area was occupied by high and low-density built-up land. At present, rice cultivation practiced on existing paddy field is still sufficient to meet demands but the study showed that land conversion has caused a significant loss of paddy fields, and thus may lead to scarcity of land suitable for rice cultivation soon in future if the current conversion trend continues. Based on ongoing trend of land demand, there will be less wet agricultural land than the required area for paddy field by 2029. The Government stated that at least 400 km2 of the paddy field should be preserved to produce enough food for the population in 2029. Under ivfarmland protection scenario, all high potential land will be secured from conversion, but still less rice field area will be available. To provide at least 400km2 in area for rice field by 2029, it is necessary to reduce land occupancy of wet agriculture area for high-density built-up area by 0.1% per year. These projection results enhance our understanding about the serious need of preserving paddy areas in the study area. In addition, the preservation effort should be combined with control in built-up area from expanding.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Natural Resources Management, School of Environment, Resources and Development
Thesis (Ph.D.) - Asian Institute of Technology, 2011
Keywords: Land use -- Indonesia -- Yogyakarta